Electricity generation and wind potential assessment in regions of colombia (2012)
In this work, mathematical modeling and simulation of electricity generation from wind was carried out in regions which are not connected to the national electrical system grid, and have an annual mean wind velocity higher than 4m/s at an altitude of 10m. Seven different types of turbines of power between 6 and 2750kW were studied to analyze their technical and economic feasibility. The Gachaneca (Boyacá) and the Sesquicentenario (Isla de San Andres) stations have an energy potential of 5106 and 3823 MWh/year, respectively, using 2750kW turbine at an altitude of 70m. The production cost of kWh for two regions was found to be less than 0.1 US$ for turbine with capacity higher than 1.0 MW. The produced energy can satisfy the electric necessities of the islands of Colombia, such as San Andres and Providencia.